Some Aspects of the Mechanism of Thrombolysis - Johnson, Alan J.; Ross McCarty, W (Thrombosis and Haemostasis, 1961)
1. Antibody to streptokinase and kinase, activator and plasmin inhibitors in the circulating blood of man, inhibit parenterally injected streptokinase and streptokinase-plasmin, in vivo. In vitro assays of these inhibitors determine the priming dose of streptokinase and streptokinase-plasmin to neutralize the inhibitors and effect thrombolysis.2. Persistent thrombolysis was produced in 16 of 21 experimentally induced thrombi in man, when streptokinase or activator was utilized. No persistent thrombolysis occurred in 9 instances, when plasmin was utilized (streptokinase-plasmin in 7 and glycerol-plasmin in 2).1. A critical amount of plasminogen was required in vivo, for effective thrombolysis (100 proactivator units). This fact demonstrates further the importance of activator in the production of thrombolysis, since activator but not plasmin requires intrinsic clot plasminogen to produce thrombolysis.